(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Mercenaries, sometimes known as soldiers of wealth, are people who actively participate in an armed conflict for personal gains or are outside the conflict; Mercenaries fight for money or other performance, they do not have principles, values or laws that govern them in the fields of conflict; According to international law, mercenaries are not considered legitimate combatants, nor are they prisoners of war. Their actions violate laws, are criminalized and require criminal accountability. Another image of the mercenary has recently appeared, represented by the private military and security companies, and reality has proven their involvement in the work of military mercenaries; This large and influential role of mercenaries is not limited to resolving the conflict in favor of one of the parties, but extends it to the nature of their activity in the battlefields, and despite the increasing condemnation, they still exist in different forms and participate in various activities.